ANALISIS PENGELOLAAN MODAL KERJA PADA KOPERASI PEGAWAI REPUBLIK INDONESIA UNIVERSITAS RIAU - Ana Putri Sianipar; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the management of working capital at the Koperasi Pegawai Republik Indonesia Universitas Riau in the 2014-2018 period. The subjects in this study were the Koperasi Pegawai Republik Indonesia Universitas Riau Unit and the object of this research was the 2014-2018 financial statements which included items in the balance sheet and income statement. The data collection method used in this research is documentation. The data analysis method used in this study is the analysis of cash turnover ratios, accounts receivable turnover, inventory turnover and working capital turnover. Based on the research results, it shows that working capital turnover, cash turnover, accounts receivable turnover and inventory turnover are categorized as very insufficient because they have not reached the cooperative measurement standard. Keywords: Working Capital Turnover, Cash Turnover, Accounts Receivable Turnover, and Inventory Turnover.